A novel efficient approach to the solution of nonlinear boundary value problems - Quang A, Dang; Dang Quang Long, (Journal of Computer Science and Cybernetics, 2025)
This paper provides an overview of a novel efficient approach to study both qualitative aspects and numerical solution of boundary value problems (BVPs) for high order nonlinear differential equations developed by the author Dang Quang A and his collaborators recently. This approach is also extended from BVPs with two-point boundary conditions to integral BVPs, and from ordinary differential equations (ODEs) to integral differential equations, functional differential equations and partial differential equations. Our published works to date demonstrate the efficiency of the approach in comparison with that of some existing methods. The approach is general and it can be applied to other nonlinear BVPs.